2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091092
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of velocity anisotropy during gastric electrical arrhythmia

Abstract: In this study, an automated algorithm was developed to identify the arrhythmic gastric slow wave activity that was recorded using high-resolution mapping technique. The raw signals were processed with a Savitzky-Golay filter, and the slow wave activation times were identified using a threshold varying method and grouped using a region-growing method. Slow wave amplitudes and velocities were calculated for all cycles. Arrhythmic events were identified when the orientation of a slow wave at an electrode exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Importantly, these slow wave initiation and conduction abnormalities may often occur within normal frequency ranges, potentially being missed by techniques lacking in spatial resolution, like cutaneous EGG [ 10 , 12 ]. GEMS analyses have also recently been applied to show, for the first time, that high-velocity and high-amplitude activity routinely emerges in association with many dysrhythmic events [ 28 , 29 ]. In future, this finding may help in the localization and treatment of dysrhythmic sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these slow wave initiation and conduction abnormalities may often occur within normal frequency ranges, potentially being missed by techniques lacking in spatial resolution, like cutaneous EGG [ 10 , 12 ]. GEMS analyses have also recently been applied to show, for the first time, that high-velocity and high-amplitude activity routinely emerges in association with many dysrhythmic events [ 28 , 29 ]. In future, this finding may help in the localization and treatment of dysrhythmic sources.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal human stomach, for example, HR mapping has recently shown that normal slow wave excitation is characterized by marked velocity and amplitude transitions occuring between the normal pacemaker region and the corpus, and within the gastric antrum [ 8 ]. Abnormally high velocity and amplitude activity has also recently been found to routinely accompany gastric dysrhythmias, and the velocity and amplitude data provided by GEMS can, therefore, assist in identifying and understanding the onset, location and pattern of abnormal events [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Amplitudes were calculated by using a peak-trough detection algorithm based on the ‘zero-crossing’ of the first and second-order signal derivatives of each event, and visualized by assigning a color gradient according to magnitude (Figure 1E) 19 . Corpus results (which show consistent velocities and amplitudes in normal circumstances 16 ) were decomposed into longitudinal and circumferential components for comparison as previously described 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Accurate determination of slow wave propagation velocities has become a central focus of gastric HR mapping analysis because substantial changes in velocity have been associated with gastric dysrhythmias indicating abnormal circumferentially propagating wavefronts [10]. Identifying velocity features may therefore allow a better understanding of dysrhythmic slow wave propagation and contribute to an improved foundation for clinically diagnosing gastric dysrhythmias using HR mapping.…”
Section: Introductionmentioning
confidence: 99%